Knowledge-intensive business services as credence goods: A demand-side approach - Daniel Feser; Till Proeger (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
Knowledge-intensive business services (KIBS) constitute a major source of innovative knowledge for small- and medium-sized enterprises. In regional innovation systems, KIBS play a crucial role in distributing innovations and improving the regions overall innovative capacities. While the specific properties and effects on client firms and sectors have been comprehensively discussed, the internal perspective of client firms, i.e. the processes and problems in selecting, using, evaluating and recommending KIBS, has been neglected to date. Using a qualitative approach, we describe the internal mechanisms and problems of SMEs cooperating with various KIBS and discuss the implications for regional innovation systems from a policy-making perspective. We find that all stages of cooperation of SMEs and KIBS are characterized by strong information asymmetries, distrust and uncertainty about the effects of using external know-how, which yields the interpretation that SMEs perceive KIBS as credence goods. While informal networks are used to reduce information barriers, they regularly prove counterproductive by disseminating worst-case examples. Regional policy aiming at developing instruments for fostering innovative cooperation could thus strengthen formal networks that primarily create trust between KIBS and SMEs to systematically reduce mutual suspicions and information asymmetries.
Keywords: D21; D40; H25; H40; L23; 330; credence goods; knowledge-intensive business services; regional innovation system; small- and medium enterprises